PENGARUH LATIHAN LEGS CIRCUITS TERHADAP KEKUATAN OTOT TUNGKAI PADA TIM BOLAVOLI PUTRI SMA N 3 PEKANBARU - Cevvin Septa Edran; Slamet '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract, The purpose of this research is to know the effects of Legs Circuits exercise toward strenght of limbs muscles of SMA N 3 PEKANBARU Women's Volleyball Team. Type of research used is experiment with One Group Preetest Posttest Only Design. the population in this research was the students of SMA N 3 pekanbaru woman’s volleyball team who actively doing exercise, the total was 8 students. sampling techniques using total sampling where the entire population sampled. The instruments was used in this research was expanding dynamometer, which is aimed to measure the strength og arm and shoulder muscles. After that, the data was analysis by using statistic to examine the normality with liliefors test on the significant level 0,05α. The subritted hypothesis was there is the effect of Leg Circuit exercise toward strength of limbs muscle. Based on the data analysis t test showed tcount was 4,55 and T table was 1,895, it means that tcount > ttable. Based on the statistic data analysis, the mean of preetest was 55,31 and the mean of posttest 61,25. In conclution , there was the effect of Leg Circuit exercise toward strength of limbs muscle of SMA N 3 woman’s volleyball club with the difference in the mean is 5.94.Keywords : Leg Circuit, Strenght limbs muscles